Environmental and Social Justice in the City: Historical Perspectives - Massard-Guilbaud, Geneviève; Rodger, Richard (The White Horse Press, 2011)
The world is full of environmental injustices and inequalities, yet few European historians have tackled these subjects head on; nor have they explored their relationships with social inequalities. In this innovative collection of historical essays the contributors consider a range of past environmental injustices, spanning seven northern and western European countries and with several chapters adding a North American perspective. In addition to an introductory chapter that surveys approaches to this area of environmental history, individual chapters address inequalities in the city as regards water supply, air pollution, waste disposal, factory conditions, industrial effluents, fuel poverty and the administrative and legal arrangements that discriminated against segments of society.